Use of laboratory incubation techniques to estimate greenhouse gas footprints from conventional and no-tillage organic agroecosystems. (September 2017) - Bhowmik, Arnab; Fortuna, Ann-Marie; Cihacek, Larry J.; Rahman, Shafiqur; Borhan, Md Saidul; Carr, Patrick M.
Abstract: Organic agroecological systems "produce goods using methods that preserve the environment" but can be a substantial source of greenhouse gases (GHG) if not managed properly. The objective of this experiment was to monitor nitrogen (N) and carbon (C) transformations in soils resulting from N additions, water filled pore space (WFPS) and prior tillage management during a simulated freeze-thaw. Incubated soils were taken from two USDA certified organic five-year small grain rotations with mixed legume cover crops that varied only in tillage, conventional (CT) vs. no-tillage (NT) for 3 yr prior to sampling. Soils incubated for 149 d were left unamended or amended with 15 N labelled urea or sugar beet residue and maintained at 40, 60 and 80% WFPS. Non-metric multidimensional scaling (NMS) verified that soils amended with beet vs urea clustered separately in ordination space. A two way PerMANOVA analysis confirmed a significant interaction between WFPS and N amendment ( p = 0.0002). Prior tillage management, N treatment and WFPS had a significant effect on GHG emission from soils. At 40% WFPS, soil previously in NT amended with beet residues emitted more nitrous oxide (N2 O) and carbon dioxide (CO2 ) relative to soil previously in CT. At 60% WFPS, soil previously in CT amended with beet residues emitted greater N2 O and less CO2 relative to soil previously in NT. Our research indicates that climate, carbon stocks and duration of prior tillage management determined the potential of no-till to reduce GHG emissions during a simulated freeze-thaw. Growers should note that as much as 4.51% of nitrates (NO3 − ) in residues can be lost as N2 O at an average soil temperature of 10 °C. Highlights: Climate, C stocks and tillage duration determined GHG losses. AOB, amoA gene copies reflect shifts in temperature, WFPS, tillage and N source. Significant N2 O can be emitted at a soil temperature of 10 °C if N is available.